Oxygen Surface Exchange Kinetics of Pr2(Ni, Co)O4+δ Thin-Film Model Electrodes. Issue 14 (1st January 2019) - Berger, Christian; Egger, Andreas; Merkle, Rotraut; Bucher, Edith; Stuhlhofer, Benjamin; Schrödl, Nina; Lammer, Judith; Gspan, Christian; Logvenov, Gennady; Maier, Joachim; Sitte, Werner
Abstract : Dense thin-film microelectrodes of the first-order Ruddlesden-Popper phases Pr2 NiO4+δ (PNO) and Pr2 Ni0.9 Co0.1 O4+δ (PNCO) were prepared by pulsed laser deposition and photolithographic patterning on yttria-stabilized zirconia (YSZ) substrates. The thin-films were characterized by X-ray diffraction, scanning electron microscopy, scanning transmission electron microscopy, inductively coupled plasma optical emission spectroscopy, energy dispersive X-ray spectroscopy and electron energy loss spectroscopy. Investigation of the phase stability of PNO and its reactivity with YSZ was performed by X-ray diffraction analyses after high-temperature treatment in air. Resistive and capacitive contributions of the individual processes occurring at the microelectrodes were determined by means of electrochemical impedance spectroscopy at various temperatures (550 ≤ T/°C ≤ 850) and oxygen partial pressures (1 × 10 −3 ≤ pO2 /bar ≤ 1). Oxygen surface exchange coefficients k q and kchem were calculated from the surface resistances and chemical capacitances of the thin-film electrodes. Comparing k q -values of PNO and PNCO shows that substitution of Ni with 10% of Co increases the oxygen surface exchange rates, especially at lower oxygen partial pressures.